Revisiting Receptive Skills in Online Learning: The Students’ Attitude - Wijaya, M Sayid; Indrasari, Nunun (English Education: Jurnal Tadris Bahasa Inggris, 2022)
This research attempts to investigate the English language learners’ attitude on the online learning of receptive skills, namely listening and reading skills, conducted in English Language Education Department of UIN Raden Intan Lampung. One hundred and twenty-four students of the first year of English Education Department participated in this descriptive quantitative research with online survey design. The data were collected by using a close-ended questionnaire of the ABC model of attitude proposed by Jain which revealed three elements; affective, behavior, and cognition. The questionnaire was administered online to the students who had experienced the process of teaching and learning online in listening and reading courses. The result showed that students’ attitude towards online learning of receptive skills indicated as positive attitude on affective aspect (x̄ = 3.04), behavioral aspect (x̄ = 3.01) and cognitive aspect (x̄ = 3.01) which concerned on the online learning platforms, task completion, lecturers’ strategies in delivering online materials, online group discussion, and receptive skills improvement. In spite of the positive results elicited from this research, there were some limitations encountered such as learning platforms provided by the lecturer, their strategies in teaching receptive skills, and task types which had not been revealed in this research. Thus, for the future research who are interested in doing research in education, it is expected to investigate those areas.